2015
DOI: 10.1108/jmtm-05-2014-0062
|View full text |Cite
|
Sign up to set email alerts
|

Improving to Smart Organization

Abstract: Purpose – The purpose of this paper is to focus on studying the concept of “Smart Organization” and providing a comprehensive framework for the various factors as barriers for the smart organization, identifying and classifying the key criterion of these factors based on their direct and indirect relationships. Design/methodology/approach – In this paper an extensive literature survey and experts’ opinion have been used to identify major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…ISM methodology is widely used to model and classify relationships among specific elements. ISM is an interactive erudition process in which a set of unlike and directly connected elements are structured into a complete methodical model (Kannan et al , 2009; Dubey et al , 2015; Sushil, 2017; Haleem et al , 2018; Saurikia et al , 2017; Khan and Haleem 2015; Khan et al , 2020a, b). ISM utilises the interrelations among the factors of the system to generate a model.…”
Section: Methodsmentioning
confidence: 99%
“…ISM methodology is widely used to model and classify relationships among specific elements. ISM is an interactive erudition process in which a set of unlike and directly connected elements are structured into a complete methodical model (Kannan et al , 2009; Dubey et al , 2015; Sushil, 2017; Haleem et al , 2018; Saurikia et al , 2017; Khan and Haleem 2015; Khan et al , 2020a, b). ISM utilises the interrelations among the factors of the system to generate a model.…”
Section: Methodsmentioning
confidence: 99%
“…This complexity is due to the presence of many impediments as well as the complicated interactions among these impediments. Not that alone, the presence of directly or indirectly related impediments complicates the issues at hand, which may or may not be expressed in an unambiguous manner [55]. Thus, it becomes quite hard to handle such problems in which the structure is not clearly defined.…”
Section: Methodsmentioning
confidence: 99%
“…Among the notable advantages of using the ISM and MICMAC techniques in this study is that the adoption of these techniques provides a more vigorous modeling of the information obtained from the experts and provides a closer and easier way to understand and appreciate the resultant information. The improvement and impact that these techniques have on the structural analysis is highly remarkable [55]. Also, these techniques permit the experts to evaluate the influence among the impediments by linguistic terms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kamble et al (2018) and Khanzode et al (2020) also explained barriers to Industry 4.0 implementation in their research. Though many authors have reported barriers of LSS (Yadav and Desai, 2017;Ben Ruben et al, 2018;Albliwi et al, 2014;McLean and Antony, 2014) and Industry 4.0 (Kamble et al, 2018;Moktadir et al, 2018;Glass et al, 2018;Raj et al, 2019;Khan and Haleem, 2015) separately in their research, very few hardly portrayed LSS barriers in the perspective of Industry 4.0. Hence, there is stringent need to study and prioritize these barriers.…”
Section: Barriersmentioning
confidence: 99%